ANALISIS MUTU PAVING BLOCK DENGAN VARIASI AGREGAT HALUS - Nofrianto, Hendri; Hutrio, Hutrio (Jurnal Teknologi dan Vokasi, 2023)
Paving block is a building material made from a mixture of cement, sand and water. Paving blocks are widely used in construction, such as sidewalks, highways, parking lots, parks and so on. Ease of installation, cheap maintenance and fulfilling the aesthetic aspects make paving blocks more popular. Along with the many uses of paving blocks in the community, the quality of paving blocks must be improved. Paving block printing uses a multi block machine. The multi block machine is a mass paving block printing machine with hydraulic power. The mold used in this study was rectangular with a size of 21 cm x 10.5 cm x 8 cm. The variation of the mixture used in this study is 1 cement: 1 filler: 3 mediums, 1 cement: 3 fillers: 1 medium, and 1 cement: 3 fillers. With each mixture having 4 samples and the age of the compressive strength test is 28 days. The average compressive strength of paving blocks at the age of 28 days with a mixture composition of 1:1:3 (1 cement: 1 filler: 3 medium) was 194.73 Kg/cm2. For paving blocks with a mixture composition of 1:3:1 (1 cement: 3 fillers: 1 medium) obtained 190.37 Kg/cm2. Meanwhile, paving blocks with a mixture composition of 1:3 (1 cement: 3 filler) were obtained at 217.76 Kg/cm2. Of the 3 variations of the mixture composition tested, the 1:3 mixture composition had the highest compressive strength with a value of 217.76 Kg/cm2. The results of the examination of porosity or water absorption on average obtained the following results. For the 1:1:3 mixture composition, the average water absorption value is 1.30%. For a 1:3:1 mixture composition, the average water absorption value is 1.21%. As for the composition of the 1:3 mixture, the average water absorption value is 1.27%. Thus, all variations of the paving block mixture have met the water absorption limit for paving blocks with quality B in SNI-03-0691-1996, which is a maximum of 6%.